The Concept and Application of Popular Sovereignty: A Comparative Study of Western Political Theory, the Indonesian Constitution, and Islamic Law in Addressing the Challenges of Contemporary Democracy - Cenedy, Robert (The Future of Education Journal, 2026)
This article presents a comparative analysis of popular sovereignty concepts from three major perspectives: Western political theory, Indonesian constitution, and Islamic law, examining their application amid contemporary democratic challenges in Indonesia. Employing a systematic qualitative-comparative approach with explicit analytical frameworks, this study delineates philosophical foundations, legitimacy sources, implementation mechanisms, and power limitations inherent to each perspective. Findings reveal that Indonesian popular sovereignty represents a unique Pancasila-based synthesis dialoguing with Western liberal traditions and Islamic principles. However, empirical evidence demonstrates fundamental challenges including pervasive oligarchy (wealth defense mechanisms), systemic corruption, identity politics mobilization, and disinformation campaigns collectively threatening democratic quality as measured by Diamond's eight dimensions. This article argues that Islamic legal principles, when interpreted progressively and contextually, can offer robust ethical frameworks to address these distortions through internalization of Islamic ethics in democratic praxis rather than sharia formalization. These findings contribute original insights by integrating sovereignty analysis with contemporary democratic challenges through an Islamic lens, filling significant gaps in comparative political theory literature.